I can’t see it is to blurry
Step-by-step explanation:
(1.7x10^4) x (8.5x10^-2)
17000 × 0.085
= 1445
No, they are not equivalent.
5(2x - y) = 10x - 5y and it is not equal to 15x - 5y.
(using distribution property)
Answer:
g(-3)=9
Step-by-step explanation:
Replace all of the (x) with -3
So the new equation
g(-3)= -2(-3)+3
Now simplify
g(-3)= 6+3
Simplify further
g(-3)= 9
Hope this helps!
The answer would be 1/p^5q^0 so Brianna is correct. If you took it a step further, the answer would be 1/p^5 because any number (except 0) or variable raised to the zero power is 1.